2007
DOI: 10.1029/2006gl028494
|View full text |Cite
|
Sign up to set email alerts
|

Subionospheric VLF observations of transmitter‐induced precipitation of inner radiation belt electrons

Abstract: [1] Ionospheric effects of energetic electron precipitation induced by controlled injection of VLF signals from a ground based transmitter are observed via subionospheric VLF remote sensing. The 21.4 kHz NPM transmitter in Lualualei, Hawaii is keyed ON-OFF in 30 minute periodic sequences. The same periodicity is observed in the amplitude and phase of the sub ionospherically propagating signals of the 24.8 kHz NLK (Jim Creek, Washington) and 25.2 kHz NLM (LaMoure, North Dakota) transmitters measured at Midway I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 25 publications
2
78
0
Order By: Relevance
“…In order to explain the existence of electron precipitation zones at middle latitudes, several hypotheses are currently under investigation (Millan and Thorne, 2007). One of these hypotheses regarding the connection with ground-based radio-transmitters has been recently confirmed (Inan et al, 2007a). Another hypothesis concerning global thunderstorms activity has also been considered and it was confirmed that lightning induces electron precipitation (Inan et al, 2007b).…”
Section: Introductionmentioning
confidence: 92%
“…In order to explain the existence of electron precipitation zones at middle latitudes, several hypotheses are currently under investigation (Millan and Thorne, 2007). One of these hypotheses regarding the connection with ground-based radio-transmitters has been recently confirmed (Inan et al, 2007a). Another hypothesis concerning global thunderstorms activity has also been considered and it was confirmed that lightning induces electron precipitation (Inan et al, 2007b).…”
Section: Introductionmentioning
confidence: 92%
“…The interaction between man-made VLF signals and energetic electrons in the magnetosphere and, in particular, the problem of wave-induced electron precipitation, have been a subject of intensive studies during the last few decades (Helliwell and Katsufrakis 1974;Karpman and Shklyar 1977;Matsumoto 1979;Southwood 1983;Albert 2001;Trakhtengerts et al 2003;Inan et al 2007). The number of papers on this problem is enormously large, and those mentioned above constitute only a small part of the papers where references to the most important studies may be found.…”
Section: Peculiarities Of Proton Resonance Interaction With Vlf Signalsmentioning
confidence: 99%
“…When detectable, higher harmonics provide useful information on propagation condition and characteristics of the lower ionosphere (Singh and Singh, 1996;Kumar et al, 2008). Barr et al (2000) Injection of VLF signals from ground based transmitters nevertheless offer more reliable choices for studying polarization effects and ionosphere anisotropy because electromagnetic source characteristics are well known (e.g., Inan et al 2007). Harrison et al (2010) suggest using tweeks to investigate possible ionospheric disturbances related to seismic activity.…”
Section: Sferics and Tweeksmentioning
confidence: 99%